Preparation of Liquid Epoxidized Natural Rubber by Oxidative Degradations Using Periodic Acid, Potassium Permanganate and UV-Irradiation - Rooshenass, Pejvak; Yahya, Rosiyah; Gan, Seng Neon (Springer, 2018)
Epoxidized natural rubber (ENR) needs to be degraded into shorter chain lengths, to form liquid epoxidized natural rubber (LENR), for applications such as coating and adhesives. Since ENR contains both C=C and epoxide groups as reactive sites for degradation reactions, thus, LENR could be prepared by different methods through cleavages of C=C or epoxide groups, or a combination of both sites. Different mechanisms would produce different terminals on the LENR. This paper reports the oxidative degradation by (a) periodic acid, (b) potassium permanganate and (c) ultra violet (UV) irradiation. The degraded rubbers were characterized by gel permeation chromatography (GPC), nuclear magnetic resonance (NMR) and Fourier transform infra-red spectroscopy (FTIR). Ester and ketone terminals were formed in all the three methods, but lactone and hydrofuranic structures were observed only in degradation by UV irradiation. NMR spectrum reveals that cyclization of ENR has occurred during degradation by periodic acid. At lower periodic acid concentration, degradation takes place only via C=C cleavage, but at higher concentration, the attack to the epoxide groups becomes more prominent. Potassium permanganate has attacked both the double bonds and epoxide groups. On the other hands, epoxide group was not affected during degradation by UV irradiation, which cleaved only the C=C bonds.